Outcomes after laparoscopic living donor nephrectomy: comparison of two laparoscopic surgeons with different levels of expertise. (3rd July 2012) - Friedersdorff, Frank; Werthemann, Peter; Cash, Hannes; Kempkensteffen, Carsten; Magheli, Ahmed; Hinz, Stefan; Waiser, Johannes; Liefeldt, Lutz; Miller, Kurt; Deger, Serdar; Fuller, T. Florian
Abstract : What's known on the subject? and What does the study add?: Laparoscopic living donor nephrectomy has evolved as the procurement method of choice for living kidney donation. Given that this is a technically challenging procedure with potential risks for the healthy donor, skills transfer from an experienced laparoscopist to a novice is critical. The present study investigates donor and recipient outcomes during a novice's early experience with this procedure. Previous training in laparoscopic renal surgery and mentoring by the expert helps the novice to generate acceptable outcomes. However, longer warm ischaemia times during the learning phase may affect short‐term graft function. Objective: To test the effect of surgeon experience on donor and recipient outcomes after laparoscopic living donor nephrectomy (LLDN). Results of a LLDN expert were compared with those of an LLDN novice. Patients and Methods: Between October 2008 and October 2010 the last 20 cases of a series of 130 consecutive LLDNs, performed by an expert (EXP) were compared with the first 20 cases of an LLDN novice (NOV). Donor and recipient outcomes were evaluated. The novice was mentored by the expert during his initial four LLDN cases. Results: Donor and recipient demographics were not different between the two surgeon groups. Total operating time and warm ischaemia time during LLDN was significantly longer in the NOV group compared with the EXP group (273 min vs 147 min and 213 s vs 162 s, respectively). The incidence of donor complications was low in both groups. Length of hospital stay among donors did not differ between groups. Although delayed graft function, rejection rates and postoperative serum creatinine levels indicated slightly poorer recipient outcomes in the NOV group, differences did not reach statistical significance. Conclusions: Mentoring by an experienced urological laparoscopist may help an LLDN novice to generate acceptable donor and recipient outcomes. Whether or not prolonged operating times and warm ischaemia times during the early phase of an LLDN experience are risk factors for impaired graft function needs further evaluation.